CAPITALISM, NATIONAL SOVEREIGNTY AND DEMOCRACY: STATE OF MORDEN LIBERAL POLITIES - Гайко, О.С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
The process of emergence and spread of national sovereignty in the context of the capitalist system is examined. Attention is concentrated on the role of capitalism in the formation of liberal democratic institutions. The basic problems of modern liberal democracies and their impact on national sovereignty are outlined.